Mathematics Education Research Food For Thought With Flavours From Asia - Allan Leslie White (Southeast Asian Mathematics Education Journal, 2013)
This paper will dip into the wonderfully rich, internationally flavoured, mathematics education research smorgasbord. In more recent times the focus has concentrated upon the cook (the teacher) and the skills needed (pedagogical knowledge) to produce delightfully pleasing brain food to nourish the growth of students. However, if this focus ignores the other essential ingredients (context, students, parents, and policies) then the results do not meet expectations. These expectations are also many and varied and include academic standards and achievement, engagement and deep understanding, exciting and enjoyable teaching and learning, relevant and meaningful learning, and the development of thinking and reasoning skills. Mathematics education research is a source of many recipes for success, and where the various countries provide their own cultural flavours. This paper will attempt to provide a taste of a range of samples drawn from research in order to satisfy an assortment of expectations while providing food for further thought.